PEMETAAN TINDAK KRIMINAL DI WILAYAH MADIUN DENGAN ANALISIS KORESPONDENSI BERGANDA - Anindia Nufitasari; Hari Wijayanto; Itasia Dina Sulvianti (MEDIA STATISTIKA, 2017)
Multiple correspondence analysis is one of the statistical methods that can be used to describe the characteristics of criminal acts. Information about charateristic of crime is necessary to reduce the number of criminal acts. The purpose of this study is to describe criminal acts in the City and District of Madiun. Data sourced from Madiun City Police Station and Madiun District Police recording during 2016. The result of the research shows that criminal acts of theft, mistreatment and fraud have similar events characteristic at public place and residential area of Madiun City and Sub Unit of Development Area 2 at 06.00-11.59. Gambling and rape also characterize similar events at the crime scene residential area Sub Unit of Development Area 3 at 18.00-23.59. Illegal logging has different characteristics than other criminal acts. Meanwhile, theft, torture, and rape have characteristics of ≤ 25 years old and education level ≥ Senior High School (SHS). But criminal acts of fraud, illegal logging, and gambling have different characteristics of the perpetrators.